2014
DOI: 10.1186/2045-709x-22-17
|View full text |Cite
|
Sign up to set email alerts
|

A survey of “mental hardiness” and “mental toughness” in professional male football players

Abstract: BackgroundIt is not uncommon for chiropractors to be associated with sports teams for injury prevention, treatment, or performance enhancement. There is increasing acceptance of the importance of sports psychology in the overall management of athletes. Recent findings indicate mental hardiness can be determined reliably using specific self-assessment questionnaires. This study set out to investigate the hardiness scores of professional footballers and examine the correlation between two questionnaires. It also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…This last work used a different mental toughness index questionnaire (Gucciardi, Hanton, Gordon, Mallett & Temby, ), and indeed this variety of instruments used is one of the main problems in studying MT (Cowden, ). However, the questionnaire used in the present study, SMTQ, has shown a good correlation ( r < 0.709, p < 0.001) with other similar instruments such as the Psychological Performance Inventory (Loehr, ), with men football players who play or had played for national teams scoring slightly higher on the mental hardiness scores (Wieser & Thiel, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This last work used a different mental toughness index questionnaire (Gucciardi, Hanton, Gordon, Mallett & Temby, ), and indeed this variety of instruments used is one of the main problems in studying MT (Cowden, ). However, the questionnaire used in the present study, SMTQ, has shown a good correlation ( r < 0.709, p < 0.001) with other similar instruments such as the Psychological Performance Inventory (Loehr, ), with men football players who play or had played for national teams scoring slightly higher on the mental hardiness scores (Wieser & Thiel, ).…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted, however, that MT may be influenced by other psychological attributes such as task and ego orientation (Álvarez, Walker & Castillo, ). With respect to studies carried out on women footballers (Danielsen et al ., ; Guillen & Santana, ; Wieser & Thiel, ), there seems to be a relationship between MT and performance, although this relationship is influenced by the player's level and age. Again, which criterion is chosen for “performance” might influence that relationship (Cowden, ).…”
Section: Discussionmentioning
confidence: 98%
“…Although the eight indicator variables from the three tools were significantly correlated with correlations ranging from 0.18 to 0.63, there was no evidence of multicollinearity as measured by the variance inflation factors which were all less than 2.39 in a regression model [ 49 ]. The SMTQ and PPI-A have been used in combination in other studies [ 15 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Components of overall MT include a combination of attributes, characteristics, and strategies[ 13 ]: goal setting, visualization, stress management, emotion control, confidence, persistence, rebounding from failure, and positive-cognition [ 14 , 15 ]. An effort to understand the factors that comprise MT in athletes and how these factors affect performance outcomes led to the development of multi-dimensional questionnaires [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among those that conducted competitive standard comparisons using total MT (N = 9) and subcomponent MT (N = 7), significant differences in total MT or at least one subcomponent were reported in 66.7% [8,29,30,35,37,38] and 71.4% [8,30,35,38,39] of the studies, respectively. In each case, the MT of athletes participating at higher levels of competition was higher.…”
Section: Mental Toughness and Competitive Standardmentioning
confidence: 99%